For or against Greed? - Mizdrak, Inga (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The phenomenon of greed can be investigated from a number of perspectives. Depending on the context, it can manifest itself in almost every aspect of social, economic and cultural life. In an age of exceptional civilisational changes, it is hard to define greed and articulate its defining features. Attempts to redefine greed in economic science are to some extent to blame. Greed is an important factor in boosting economies. In the social sciences, it can be cast as as a natural sign of consumerism.The aim of the paper is to present greed in two contexts: of human subjectivity and various “cracks” caused by greed. Spiritual, volitional, emotional and intellectual layers are destabilised by greed, which is initiated by the subject, thus weeding out the important role of internal self-development (especially in the moral sense). Through the analyses of Erich Fromm, Tomáš Sedláček, Michael Sandel and Benjamin Barber, greed is presented from an economic-ethical-anthropological perspective, and ultimately as leading to the imprisonment of the individual. The analyses also reveal a perspective on interpersonal relations eliminating the possibility of acting collectively on the basis of justice, fair exchange and solidarity.